PERBANDINGAN WAKTU ENKRIPSI ANTARA METODE ELECTRONIC CODEBOOK (ECB) DAN CHIPHER BLOCK CHAINING (CBC) DALAM ALGORITMA BLOWFISH - Ida Ayu Widyantari Arnawa Putu Eka Widastra Hary C. A. A. Gede Bimantara Putra (JURNAL ILMU KOMPUTER INDONESIA, 2020)
Along with the development of the world of technology and information, cryptography becomes very important because cryptography is widely used to maintain the confidentiality and security of information. Optimization of the work of cryptography, needs to be supported by supporting algorithms. The development of supporting algorithms for cryptography has been very much developed and implemented. The block chipper algorithm was developed in line with developments in the technological era. The discovery of the Blowfish algorithm began to be analyzed again so that the longer the algorithm began to be accepted as an encryption algorithm that has a high level of security. In implementing the blowfish algorithm requires a large memory so that the utilization of large memory will have an impact on the execution time of the algorithm. Based on the results of the implementation and testing of the blowfish algorithm method, the ECB method requires a faster time to do text encryption when compared to using the CBC method. So that this can be taken into consideration in the selection of the right method for using the blowfish algorithm.